STRATEGI BERSAING JASA NON KLASIFIKASI PADA PT BIRO KLASIFIKASI INDONESIA - Wardhana, Aditya; Kartawinata, Budi Rustandi; Syahputra, Syahputra (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2016)
The purpose of this study was to compete formulating global strategy PT Biro Klasifikasi Indonesia (BKI) in non-classification marine services business (independent assurance) in Indonesia that includes three business sector such as marine, industry, and energy. The methodology used the analytical descriptive method with techniques SWOT analysis. The number of population as many as 5.248 companies, the target population was the BKI non-classification customers (non-klas) or independent assurance in all three business sector susch as marine, industry, and energy. The determination of the total sample using Slovin formulas with the levels of trust 95 % obtained the total sample as many as 400 respondents. The research results showed that based on a position map of non-classification services business,Â BKI was on strategic rapid growth. BKI increased the number of a new job, increased new consumer on the non-classification services (independent assurance) in all business sectors, and focused on the type of non-classification service business certain having the the highest value income for BKI.